Six Months of Inspiratory Muscle Training to Lower Blood Pressure and Improve Endothelial Function in Middle-Aged and Older Adults With Above-Normal Blood Pressure and Obstructive Sleep Apnea: Protocol for the CHART Clinical Trial - Tavoian, Dallin; Ramos-Barrera, Lupita E.; Craighead, Daniel H.; Seals, Douglas R.; Bedrick, Edward J.; Alpert, Joseph S.; Mashaqi, Saif; Bailey, E. Fiona (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiovascular disease is a major global health concern and prevalence is high in adults with obstructive sleep apnea (OSA). Lowering blood pressure (BP) can greatly reduce cardiovascular disease risk and physical activity is routinely prescribed to achieve this goal. Unfortunately, many adults with OSA suffer from fatigue, daytime sleepiness, and exercise intolerance—due to poor sleep quality and nocturnal hypoxemia—and have difficulty initiating and maintaining an exercise program. High-resistance inspiratory muscle strength training (IMST) is a simple, time-efficient breathing exercise consistently reported to reduce BP in small, selective groups of both healthy and at-risk adults. Herein we present the study protocol for a randomized clinical trial to determine the long-term efficacy of IMST performed regularly for 24 weeks in middle-aged and older adults with OSA. The primary outcome is casual systolic BP. Secondary outcomes are 24-h systolic BP and circulating plasma norepinephrine concentration. Other outcomes include vascular endothelial function (endothelial-dependent and -independent dilation), aortic stiffness, casual and 24-h diastolic BP, and the influence of circulating factors on endothelial cell nitric oxide and reactive oxygen species production. Overall, this trial will establish efficacy of high-resistance IMST for lowering BP and improving cardiovascular health in middle-aged and older adults with OSA. Methods: This is a single-site, double-blind, randomized clinical trial. A minimum of 92 and maximum of 122 male and female adults aged 50–80 years with OSA and above-normal BP will be enrolled. After completion of baseline assessments, subjects will be randomized in a 1:1 ratio to participate in either high-resistance or sham (low-resistance) control IMST, performed at home, 5 min/day, 5 days/week, for 24 weeks. Repeat assessments will be taken after the 24-week intervention, and after 4 and 12 weeks of free living. Discussion: This study is designed to assess the effects of 24 weeks of IMST on BP and vascular function. The results will characterize the extent to which IMST can reduce BP when performed over longer periods (i.e., 6 months) than have been assessed previously. Additionally, this study will help to determine underlying mechanisms driving IMST-induced BP reductions that have been reported previously. Clinical Trial Registration: This trial is registered with ClinicalTrials.gov (Registration Number: NCT04932447; Date of registration June 21, 2021).